Are Serotonergic System Genes Associated to Smoking Cessation Therapy Success in Addition to CYP2A6? - Verde, Z.; Santiago, C.; Rodríguez González-Moro, JM.; de Lucas Ramos, P.; López Martín, S.; Bandrés, F.; Lucia, A.; Gómez-Gallego, F. (Pharmacopsychiatry, 2014)
Despite progress made in the treatment of tobacco dependence, currently available treatments are effective for only a fraction of smokers. The aim of this study was to evaluate the association between the effectiveness of treatment with nicotine or bupropion in heavy smokers (n=70), and 6 candidate polymorphisms in CYP2A6, 5-HTT and HTR2A genes. Analysis revealed a significant association between “favourable” genotype combination carriers (CYP2A6 “slow metabolizer” or 5HTT L-allele or HTR2A-1438GG) and nicotine treatment outcome (OR=2.69, 95% CI=1.28–5.64). Genetic variations in CYP2A6 gene or genotypes associated with reduced synaptic serotonin activity may influence the success of smoking cessation treatment.
Keywords: nicotine; bupropion; CYP2A6; 5-HTT LPR; HTR2A-1438A>G